Design, Synthesis, and Preliminary Antiproliferative Evaluation of 1,2,4-Thiadiazole Derivatives as Possible Histone Deacetylase Inhibitors - Rusul Mohammed Hasan Ali; Al-Hamashi, Ayad (Iraqi Journal of Pharmaceutical Sciences, 2025)
Histone deacetylases (HDACs) are a class of proteins that responsible of the hydrolysis of N-acetyl lysine residues in histones as well as non-histone protein substrates. This phenomenon may provide an explanation for the involvement of these enzymes in a wide range of clinical situations, encompassing cancer, metabolic, cardiovascular problems, and neurological diseases. Most of HDAC inhibitors are often used in clinical settings consist of a hydroxamate group (ZBG) that binds to zinc ion inside the active site. The poor selectivity and pharmacokinetic characteristics of numerous medicines belonging to the hydroxamates group have prompted the exploration of non-hydroximic ZBG HDAC inhibitors with a potential selectivity and potency profile. Therefore, the objective of this work is to design new HDAC inhibitors incorporating thiadiazole moiety as a ZBG. This study involved the design and virtual analysis of a series of thiadiazole derivatives using Maestro software. Compounds with good docking score which include compound 6a [4- (benzyloxy)-N-(1,2,4-thiadiazol-5-yl)benzamide] with docking score -8.953 kcal/mol and compound 6b [4-(naphthalen-1-ylmethoxy)-N-(1,2,4-thiadiazol-5- yl)benzamide] with docking score -9.290 kcal/mol  and compound 6c[ 4-((4-methoxybenzyl)oxy)benzoic acid] with docking score -8.57 kcal/mol while the FDA approved vorinostat has a docking score -5.613 kcal/mol against HDAC 2 (4LXZ). Compound 6a, 6b and 6c were subjected to the organic synthesis applying traditional chemical reactions. The synthesis was commenced with the ether formation using Williamson reaction by reacting benzylic bromide derivatives with methyl 4-hydroxybenzoate, then the intermediates underwent ester hydrolysis to produce 4-(benzyloxy)benzoic acid derivatives and then reacted with 1,2,4-thiadiazol-5- amine by forming amide using 1-Ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC) as coupling reagent. The intermediates and final products were characterized by FT-IR and NMR spectroscopy. The cytotoxic effect was assessed using the MTT cell viability assay indicate that IC50 of 6b is 0.66 μM while the IC50 of vorinostat is 1.48 μM.